Characterization of yeast protein Deg1 as pseudouridine synthase (Pus3) catalyzing the formation of Ψ38 and Ψ39 in tRNA anticodon loop - Lecointe, François; Simos, Geōrgios; Sauer, Anke; Hurt, Ed; Motorin, Yuri; Grosjean, Henri (The journal of biological chemistry, 1998)
The enzymatic activity of yeast gene product Deg1 was identified using both disrupted yeast strain and cloned recombinant protein expressed in yeast and in Escherichia coli. The results show that the DEG1-disrupted yeast strain lacks synthase activity for the formation of pseudouridines Ψ38and Ψ39 in tRNA whereas the other activities, specific for Ψ formation at positions 13, 27, 28, 32, 34, 35, 36, and 55 in tRNA, remain unaffected. Also, the His6-tagged recombinant yeast Deg1p expressed in E. coli as well as a protein fusion with protein A in yeast display the enzymatic activity only toward Ψ38 and Ψ39 formation in different tRNA substrates. Therefore, Deg1p is the third tRNA:pseudouridine synthase (Pus3p) characterized so far in yeast. Disruption of theDEG1 gene is not lethal but reduces considerably the yeast growth rate, especially at an elevated temperature (37 °C). Deg1p localizes both in the nucleus and in the cytoplasm, as shown by immunofluorescence microscopy. Identification of the pseudouridine residues present (or absent) in selected naturally occurring cytoplasmic and mitochondrial tRNAs from DEG1-disrupted strain points out a common origin of Ψ38- and Ψ39-synthesizing activity in both of these two cellular compartments. The sensitivity of Pus3p (Deg1p) activity to overall three-dimensional tRNA architecture and to a few individual mutations in tRNA was also studied. The results indicate the existence of subtle differences in the tRNA recognition by yeast Pus3p and by its homologous tRNA:pseudouridine synthase truA from E. coli (initially called hisT or PSU-I gene product).